Chemotherapy-induced cardiotoxicity at the Instituto Nacional de Enfermedades Neoplásicas 2012-2016 - Ruiz-Mori, Enrique (2017)
Objective: To report the frequency of cardiac adverse effects (cardiotoxicity) induced by chemotherapy in patients of the Instituto Nacional de Enfermedades Neoplásicas during the period 2012-2016. Materials and methods: The study had a non-experimental, descriptive and retrospective design. The study population consisted of patients treated at the Cardiology Service due to cardiovascular discomfort during chemotherapy. Results: Nine hundred eighty-five (985) evaluations were performed because of cardiac symptoms in patients undergoing antineoplastic treatment. Among the oncological treatment-related cardiovascular adverse effects, cardiac arrhythmias were the most frequent ones (41.2%), episodes of angina pectoris were in the second place with 18.7%, and heart failure had a frequency of 4.9%. The most frequent arrhythmia was sinus bradycardia (55.9%), followed by symptomatic sinus tachycardia (17.7%) and, in the third place, atrial fibrillation (12.0%). Conclusions: Cardiac arrhythmia was the most frequent adverse effect induced by oncological treatment, with asymptomatic sinus bradycardia being the most prevalent one.